Pelaksanaan Ekstrakurikuler Marching Band di SMA Negeri 5 Payakumbuh - Rafina Tari; Harisnal Hadi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the Implementation of Marching Band Extracurricular Activities at SMA N 5 Payakumbuh. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and mobile phones. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data collection, clarification process and verification process. The results of the study show that the Marching Band extracurricular activities at SMAN 5 Payakumbuh currently show high consistency. There was no significant change in the implementation of this activity, both in terms of programs and methods. This extracurricular activity continues to run smoothly and regularly. The limitations of facilities and infrastructure are not a significant problem in the implementation of this extracurricular. This is due to the support from the City of Payakumbuh which provides the necessary tools for the Marching Band activities. This support allows extracurricular activities to continue to run without any significant constraints related to facilities.